Legal Study of Users of Prostitution Services Online According to Indonesian Legislation - Rolinka Maryonza; M. Arafat Hermana; Ana Tasia Pase (JURNAL HUKUM SEHASEN, 2023)
The internet is no longer just a necessity, but has also become a way of life for the people. The internet does not only have a positive side, such as Email, Facebook, E-Learning, E-Banking and E-Government, cyberspace also has a negative impact with the development of cybercrime, including in the field of decency, such as cyberporn, cyber prostitution, online sex and cybersex. Prostitution not only has an impact on those who do it, namely the behavior and service users, but also has an impact on the wider community. The purpose of this research is to find out the legal arrangements and legal studies on users of online prostitution services according to statutory regulations. The research method used in this research is normative research with a statutory approach and so on. Furthermore, the results of research and discussion, namely regulation and legal review are positive laws that regulate online prostitution, namely the Criminal Code, Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 44 of 2008 concerning Pornography. The punishment regulated in the above law explains only the punishment for service providers. The law does not regulate criminal provisions for service users in online prostitution crimes.